Economics of Education and Sustainable Development - Lin, Tin-Chun (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book consists of articles that investigate and discuss the relationship between economics of education and sustainable development; that is, how education economics plays an important role in sustainable development. Economics of education or education economics is the study of economic issues relating to education (such as education policy and finance, human capital production and acquisition, and the returns to human capital); while sustainable development is the study of a system (a human society) operating and growing continuously, which includes environment, economy, industry, business, agriculture, etc. This book particularly focuses on the economy - how an economy continuously and steadily develops and grows.